The Impact of Artificial Intelligence on Strategic Decision-Making in Organizations: A Case Study Approach (International Journal of Multidisciplinary and Applied Studies, 2025)
The research examines the effect that Artificial Intelligence (AI) brings to organizational strategic decision-making processes. Three large corporations from technology, retail and manufacturing segments serve as the basis to study AI tool integration through case study methods. This research demonstrates that AI improves both organizational decision speed and precision along with impacting the shape of strategic planning at the organizational level. The excessive dependence on AI systems showed potential negative effects on human strategic assessment capabilities as well as creativity in extended planning decisions during study analysis. This research delivers crucial guidance to businesses that want to apply AI for strategic decision support within their organizational framework.